Landscape and Dynamics of Single Immune Cells in Hepatocellular Carcinoma - Zhang, Qiming; He, Yao; Luo, Nan; Patel, Shashank J.; Han, Yanjie; Gao, Ranran; Modak, Madhura; Carotta, Sebastian; Haslinger, Christian; Kind, David; Peet, Gregory W.; Zhong, Guojie; et al. (Cell, 2019)
The immune microenvironment of hepatocellular carcinoma (HCC) is poorly characterized. Combining two single-cell RNA sequencing technologies, we produced transcriptomes of CD45+ immune cells for HCC patients from five immune-relevant sites: tumor, adjacent liver, hepatic lymph node (LN), blood, and ascites. A cluster of LAMP3+ dendritic cells (DCs) appeared to be the mature form of conventional DCs and possessed the potential to migrate from tumors to LNs. LAMP3+ DCs also expressed diverse immune-relevant ligands and exhibited potential to regulate multiple subtypes of lymphocytes. Of the macrophages in tumors that exhibited distinct transcriptional states, tumor-associated macrophages (TAMs) were associated with poor prognosis, and we established the inflammatory role of SLC40A1 and GPNMB in these cells. Further, myeloid and lymphoid cells in ascites were predominantly linked to tumor and blood origins, respectively. The dynamic properties of diverse CD45+ cell types revealed by this study add new dimensions to the immune landscape of HCC. [Display omitted] •Two scRNA-seq platforms reveal a high-resolution dynamic immune landscape in HCC•LAMP3+ DCs, arising from cDCs, can migrate from tumors to hepatic lymph nodes•Paired ligand-receptor analyses implicate the regulation of lymphocytes by LAMP3+ DCs•Macrophage subsets in tumors show distinct states and potentials to egress to ascites Integrated single-cell RNA sequencing technologies and bioinformatics approaches reveal a high-resolution immune landscape of hepatocellular carcinoma, identifying inflammatory signatures and functional states of myeloid cells as well as predictions of complex cell-cell interactions.